Guaranteed Wages and Unemployment Insurance in Canada - Owen, C. F . (Relations industrielles / Industrial Relations, 1955)
SummaryThe emergence of guaranteed wage plans in the automobile industry, likely to spread to other fields in the near future, poses the problem of the relationship between such plans and the national Unemployment Insurance system in Canada. This article is an attempt to indicate, by a comparative analysis of Canadian and U.S. Unemployment Insurance systems, to what extent problems associated with U.S. unemployment insurance systems, and the possible integration of these systems with company supplemental unemployment benefit plans, are applicable to Canada.